Health promotion at the local level sports clubs : applying health promoting sports club standards in the Netherlands - Alberts, Kimberly (2014)
This study explores health promotion activity of Dutch sports clubs by using the Health Promoting Sports Clubs (HPSC) standards, which are developed in Finland and here applied to the Dutch sports context. The standards consist of 23 items which cover different perspectives on health promotion. The standards form an overall HPSC index, which is used to create health promotion profiles for the sports clubs. 17 sports clubs from the municipality of ‘s-Hertogenbosch participated in this study, of which 42 club officials (1-6 per club) evaluated their own club on all HPSC standards on a five-point Likert scale. Per club, the average score on each standard was calculated. The average on the HPSC index was 9.00 ± 4.36 (range 0-23). This suggests that the participating sports clubs are positively oriented to health promotion. However, there is much room for improvement within the clubs. More research is needed to be able to generalize the results to different types of clubs, and to explore practical implications of the results.